2016
DOI: 10.1007/s00253-016-7611-8
|View full text |Cite
|
Sign up to set email alerts
|

Rhodotorula glutinis—potential source of lipids, carotenoids, and enzymes for use in industries

Abstract: Rhodotorula glutinis is capable of synthesizing numerous valuable compounds with a wide industrial usage. Biomass of this yeast constitutes sources of microbiological oils, and the whole pool of fatty acids is dominated by oleic, linoleic, and palmitic acid. Due to its composition, the lipids may be useful as a source for the production of the so-called third-generation biodiesel. These yeasts are also capable of synthesizing carotenoids such as β-carotene, torulene, and torularhodin. Due to their health-promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
142
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(153 citation statements)
references
References 117 publications
(153 reference statements)
4
142
0
7
Order By: Relevance
“…Outside of wine, Rhodotorula spp. have received considerable research attention owing to a high accumulation of fatty acids and carotenoids (reviewed by Ageitos et al ., ; Frengova and Beshkova, ; Kot et al ., ). Some Rhodotorula species, particularly R .…”
Section: Rhodotorula Sppmentioning
confidence: 97%
See 1 more Smart Citation
“…Outside of wine, Rhodotorula spp. have received considerable research attention owing to a high accumulation of fatty acids and carotenoids (reviewed by Ageitos et al ., ; Frengova and Beshkova, ; Kot et al ., ). Some Rhodotorula species, particularly R .…”
Section: Rhodotorula Sppmentioning
confidence: 97%
“…Outside of wine, Rhodotorula spp. have received considerable research attention owing to a high accumulation of fatty acids and carotenoids (reviewed by Ageitos et al, 2011;Frengova and Beshkova, 2009;Kot et al, 2016). Some Rhodotorula species, particularly R. glutinis and R. turoloides, can accumulate up to 66 and 76%, respectively, of their dry weigh as lipids (Ageitos et al, 2011).…”
Section: Rhodotorula Sppmentioning
confidence: 99%
“…It is worth noting that the strain R. glutinis ATCC 204091 (also reported as Rh. toruloides ATCC 204091 and used in this study) only accumulated 25–42% oils in the cell mass from different studies [ and references therein]. However, a recent study reported a 77% oil content with R. glutinis ATCC 204091 through a two‐step cultivation strategy .…”
Section: Resultsmentioning
confidence: 91%
“…Rhodotorula is included in the order Sporidiobolales , class Microbotryomycetes , and phylum Basidiomycota in the Fungi kingdom [1]. Species of this genus are ubiquitous saprophytic yeasts that can be acquired from many environmental sources including air, soil, grass, lakes, oceans, food, and human skin [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Species of this genus are ubiquitous saprophytic yeasts that can be acquired from many environmental sources including air, soil, grass, lakes, oceans, food, and human skin [1,2]. Rhodotorula ’ s biomass can also be a valuable addition to animal feed because these strains synthetize carotenoids: β-carotene, torulene, and torularhodin (a typical feature of this species is red colour of cells) [3,4].…”
Section: Introductionmentioning
confidence: 99%